Síndrome metabólico en niños : problemática, componentes y criterios diagnósticos (2015)
ABSTRACT: The metabolic syndrome in children increases the risk for type 2 diabetes and cardiovascular disease in adulthood. Aim: To describe the components of metabolic syndrome in children, their prevalence, and diagnostic criteria proposed by different authors and organizations. Materials and methods: A literature search of articles published in Pubmed, Science Direct, Embase, Lilacs and Scielo databases was conducted. Results and discussion: Several organizations have established definitions for metabolic syndrome diagnosis in children, some including criteria used for adults or adopting cutoffs derived from selected populations such as obese children or without including pre-adolescent children, arguing a low prevalence of alterations in these. Thus, the prevalence of metabolic syndrome in a particular population varies (0,9% to 11,4%) according to the definition used. However, this prevalence increases according to the obesity grade, and a high prevalence in pre-pubers has been reported, independent of the classification used. Recently, it was proposed the use of a continuous score to improve the metabolic syndrome evaluation in children. Conclusion: The cutoffs currently used give different weighting for each component of metabolic syndrome. Therefore, it is recommended the use of percentiles according to sex and age and population for each component and to evaluate the utility of continuous scores in this population.